Biomechanical effects of attachment designs in maxillary first molar mesialization with clear aligners: a finite element study - Vatansever, Resul; Gurel, Hakan Gurcan; Koc, Osman (SPRINGER, 2025)
BackgroundClear aligners face biomechanical limitations in complex tooth movements, particularly first molar mesialization, despite attachment use. Finite element analysis (FEA) can elucidate optimal attachment designs for force delivery.ObjectivesTo compare displacement patterns and stress distribution during maxillary first molar mesialization using four attachment designs via 3D FEA.MethodsA maxillary model (MRI-derived) was created with periodontal ligament (PDL), alveolar bone, and clear aligner (0.75 mm thickness). Five scenarios were simulated: no attachment (Model-I), vertical rectangular (Model-II), horizontal rectangular (Model-III), optimized double semi-ellipsoidal (Model-IV), and Yin-Yang attachments (Model-V). Mesial displacement (0.5 mm) was applied, and deformation/stress were analyzed using ANSYS Workbench.ResultsModel-IV (optimized attachment) demonstrated the least first molar tipping, evidenced by its lowest total mesial crown displacement (0.319 mm), and provided the best mesiodistal control. Conversely, Model-I (no attachment) exhibited the highest tipping, with a total mesial crown displacement of 0.376 mm. Yin-Yang attachments (Model-V) significantly reduced buccal displacement by 92% compared to Model-I. Horizontal rectangular attachments minimized rotational movement.ConclusionsOptimized double semi-ellipsoidal attachments provide superior first molar mesialization control, while Yin-Yang designs enhance buccal-lingual stability. Attachment geometry critically influences aligner efficacy.
Keywords: Clear aligners; Finite element analysis; Molar mesialization; Orthodontic attachments; Biomechanics; TOOTH MOVEMENT; Dentistry, Oral Surgery & Medicine